Experimental study of hydrogen production process with aluminum and water. (21st May 2020) - Bolt, Andre; Dincer, Ibrahim; Agelin-Chaab, Martin
Abstract: This study reported a novel hydrogen production experimental set up, which utilizes the chemical reaction between aluminum and water to produce hydrogen. The developed experimental setup had an aluminum powder spraying subsystem integrated within the overall setup. The effectiveness of this hydrogen production experimental set up was improved using 149-μm aluminum powder, and nitrogen gas as the medium to facilitate the spraying of the aluminum powder. Furthermore, the study utilized sodium hydroxide as the reaction promoter. The various experimental conditions implemented during the testing process included changes in the water temperature and system inputs. The criteria used to evaluate the system performance were the hydrogen yield and hydrogen production rate. The tap water was able to achieve a full hydrogen yield due to its composition, however, the 50% increase in NaOH mass trial was able to achieve a higher yield of 97.15% and 95.44% for the 3g and 6g aluminum sample test respectively. Furthermore, seawater was found to achieve a yield of 58.8%, which can be considered a viable option for future testing. Furthermore, seawater's abundance also adds to its viability for future testing. Also, the study results showed that an increase in reaction temperature best facilitates a chemical reaction taking place. This was evident during the staring temperature of the water test for the 6g aluminum samples. For instance, the maximum hydrogen production rate for the 70 °C was 35.04 mL/s, while the smallest peak for hydrogen production rate was observed using the 40 °C as the starting temperature. The 40 °C test produced a maximum hydrogen production rate value of 27.99 mL/s. Highlights: A novel method of hydrogen production with aluminum and water is experimentally developed. Sodium hydroxide is used as the reaction promoter for better performance. The maximum hydrogen production rate is achieved at a temperature of 70 °C.